A CRITICAL REVIEW STUDY ON ANATOMICAL ASPECTS OF GUPTASANA - Choudhary, Dharmendra; Yadav, Sunil Kumar; Kumar, Praveen (International Research Journal of Ayurveda & Yoga, 2019)
Yoga is one of the most powerful drugless system of treatment. It is having its own concept of wellness which has been scientifically understood and presented by many. Yoga can be adopted as lifestyle for promoting our physical and mental health.Yoga helps in the development of strength, stamina, endurance and high energy at physical level. It also empowers oneself with increased concentration, calm, peace and contentment at mental level leading to inner and outer harmony.Guptasana is a seated Yoga posture that stretches several parts of the body simultaneously. Knowledge of anatomy will help to reassure people and guide them towards rehabilitation and a better lifestyle.